STUDI EMPIRIS AUDITOR SATUAN PENGAWASAN INTERNAL PERGURUAN TINGGI NEGERI DI SERANG: PENGARUH PENGALAMAN KERJA, KOMPETENSI AUDITOR INTERNAL, INDEPENDENSI TERHADAP DUE PROFESSIONAL CARE DAN IMPLIKASINYA DALAM KUALITAS AUDIT INTERNAL - Kurniasih Dwi Astuti; Fara Fitriyani (Tirtayasa Ekonomika, 2017)
The purpose of this study is to determine the effect of work experience, internal auditor competence, independence with due professional care and its implications in the quality of internal audit at Internal Auditors State University in Serang. The Analysis of the study was conducted using SEM with smartPLS software (Partial Least Square). The results of this study indicate that (1) the internal auditor's competence variable has a significant positive effect on the due professional care, (2) the independence variable has a significant positive effect on the due professional care, (3) the professional variables have a significant positive effect on the quality of internal audit , (4) the internal auditor's competence variable has a significant positive effect on the quality of internal audit, (5) the variable of independence has a significant positive effect on the quality of internal audit, and (6) the variable of work experience has a significant positive effect on the quality of internal audit.